Going Public and the Internal Organization of the Firm - Bias, Daniel; Lochner, Benjamin; Obernberger, Stefan; Sevilir, Merih (Journal of Finance, 2025)
This paper examines how initial public offerings (IPOs) affect firms' internal organization. We find that IPO firms become more hierarchical and standardized organizations, characterized by additional layers, more managers, smaller control spans, and larger administrative functions. These changes occur mostly in preparation for the IPO and can be only partially explained by growth. IPO firms with greater human capital risk experience larger hierarchical changes. Hierarchical changes help firms standardize employee roles and formalize internal processes. Our results suggest that firms reorganize to reduce their dependence on key individuals' human capital when transitioning to public market